Impact of Oil Price Increases on U.S. Economic Growth: Causality Analysis and Study of the Weakening Effects on the Relationship - FARHANI, Sahbi (International Journal of Energy Economics and Policy, 2012)
The two oil shocks of the 1970s reduced the GDP growth rate, and since that period, sudden oil price increases have been considered as a major source of economic slowdown in the world. We thus estimate simple linear regression model (SLRM), dynamic regression model (DRM) and VAR model to evaluate the impact of oil price increases on the U.S economic growth. Our results indicate strong weaknesses on the relation between these two factors in what way that the relation has had a low significant effect caused by the existence of breakpoints and the asymmetric effects of the oil price variations. Keywords: Oil shocks; GDP growth rate; SLRM; DRM; VAR model; Breakpoints; Asymmetrical effects. JEL Classifications: C22; E31; Q43